Aspects of Personal Safety while Sailing for Fishermen in Jember Regency - Indrayani, Reny Indrayani; Ana Islamiyah Syamila; Anita Dewi Prahastuti Sujoso; Ragil Ismi Hartanti (Universitas Nahdlatul Ulama Surabaya, 2023)
Fishermen have an important role in supporting the Indonesian economy. On the other hand, fishing was the most dangerous job in the world with a very high risk of accidents and death. Therefore, it was necessary to study the safety aspects of fishermen as a basis for formulating protection policies for fishermen. This study aimed to examine aspects of personal safety when sailing for fishermen in Jember Regency. This research was a descriptive research. The research was conducted in Jember Regency in August-October 2022 involving 260 fishermen as respondents. Research data collected through interviews. Data were analyzed and presented using tables and cross-tabulations accompanied by narration. The results of this study indicated that there is a tendency that the older the respondents were, the more they pay attention to aspects of personal safety while sailing and the higher the education level of the respondents, the higher the awareness of personal safety while sailing. The government needs to work on improving personal safety aspects for fishermen, especially in terms of providing and using PPE.